Коронация, или последний из романов - Акунин Борис (Новый детективъ, 2009)
Экземпляры: ф-1 (20200206) / Инвентарный номер: 54767 / Цена: 70.00 / Сис.шифр: Р2 / Авт.знак: А 44 / ГРНТИ: 17 / ББК: 84 (2Рос=Рус)6